Open-pit overburden dump characterization using digital image processing technique - Koner, Radhakanta; Chand, Kapoor; Kumar Mankar, Amit (Wroclaw University of Technology, 2024)
The safety of the open-pit overburden dump slope largely depends on the geomaterial size and shape. The shape of these geomaterials contributes to their shear resistance against sliding. The present investigation proposed a method to characterize the geomaterial using the digital image processing tech-nique. The resources invested in this work are a simple digital camera and a computational toolbox. The system estimates the size distribution of geomaterial. The study also proposed a methodology for recon-structing the 3D geometry of the mine dump from the images. The advantage of the method is a low-cost, quick assessment of the dump geomaterial, and outcomes can easily be used in a numerical toolbox. The study was conducted in Barakar Valley Coalfields, West Bengal, India. The geomaterials above 4 mm sizes are considered in this work. The results matched the mechanical sieving output of the particle size distribution curve.
Mining Science, Vol. 31, 2024, s. 81-101
Keywords: mining; geology; geo-engineering